2015
DOI: 10.1177/1971400915609340
|View full text |Cite
|
Sign up to set email alerts
|

Novel brain MRI abnormalities in Gitelman syndrome

Abstract: Gitelman syndrome is an autosomal recessive renal tubular disorder characterized by hypokalemic metabolic alkalosis, hypomagnesemia and hypocalciuria. The syndrome is caused by a defective thiazide-sensitive sodium chloride co-transporter in the distal convoluted tubules of the kidneys. Gitelman syndrome could be confused with Bartter syndrome; the main differentiating feature is the presence of low urinary calcium excretion in the former. Descriptions of neuroradiological imaging findings associated with Gite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
4
0
5
Order By: Relevance
“…A less common association is seen with empty sella syndrome in 2 patients. Seizure disorder as a possible association with GS was previously reported in only one case by Beltagi et al, most likely due to hypomagnesemia [15]. Our patient, however, was unique with no prior history of epilepsy and had a seizure as the very first presentation with normal magnesium levels.…”
Section: Results and Statistical Analysismentioning
confidence: 59%
See 2 more Smart Citations
“…A less common association is seen with empty sella syndrome in 2 patients. Seizure disorder as a possible association with GS was previously reported in only one case by Beltagi et al, most likely due to hypomagnesemia [15]. Our patient, however, was unique with no prior history of epilepsy and had a seizure as the very first presentation with normal magnesium levels.…”
Section: Results and Statistical Analysismentioning
confidence: 59%
“…Our case reports are unique in this sense that the patient of GS presented with seizure despite having normal serum magnesium levels. In our literature review, only one patient who was reported by Beltagi et al [15] presented with somnolence and altered mental status and had a focal seizure as a complication. Even in that case, hypomagnesemia can be considered as the cause of epileptiform activity on EEG.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Мы впервые в отечественной педиатрической нефрологии наблюдали редкую форму тубулопатии -атипичный синдром Гительмана с церебральными кальцификатами. В зарубежной литературе нам встретились единичные работы, в которых описывается кальцификация базальных ганглиев у пациентов с данным синдромом [9,12,[19][20][21][22]. A. Beltagi и соавт.…”
Section: Discussionunclassified
“…A. Beltagi и соавт. (2015) трактовали церебральные кальцификаты при синдроме Гительмана как следствие энцефалопатии при митохондриальной цитопатии [12]. Под нашим наблюдением находились 4 пациента с синдромом Гительмана, у одного из них выявлена атипичная форма с церебральными кальцификатами.…”
Section: Discussionunclassified